Isolated cardiac involvement of a primary myeloid sarcoma: a case report of an unusual cause of pulmonary oedema. Issue 3 (18th February 2023) - Salisbury, Thomas; Al-Mohammad, Abdallah; Pirzada, Omar
Abstract: Background: Myeloid sarcoma, also known as chloroma, is a pathologic diagnosis for an extramedullary proliferation of blasts of one or more of the myeloid lineages. It is an uncommon manifestation of acute myeloid leukaemia (AML), although the diagnosis may occur prior to or after diagnosis of AML. Cardiac infiltration by myeloid sarcoma is extremely rare, and of the few published cases, a diagnosis of leukaemia was almost always already present. Case summary: This is a 52-year-old patient admitted to the hospital with acute shortness of breath, with a large amorphous mass found on computed tomography scan invading the myocardium and causing heart failure. Echocardiography demonstrated multiple cardiac masses. A bone marrow biopsy was non-diagnostic. An endomyocardial biopsy confirmed a cardiac primary myeloid sarcoma. The patient was successfully treated with chemotherapy with complete resolution of the cardiac infiltration and of the heart failure. Discussion: We present this rare case of primary cardiac myeloid sarcoma and discuss current literature relevant to this effectively unique presentation. We discuss the use of endomyocardial biopsy in the diagnosis of cardiac malignancy and the advantages of early diagnosis and management of this unusual cause of heart failure.